Outcome of coronary endarterectomy with off-pump coronary artery bypass grafting: A retrospective study - Redoy Ranjan; Asit Baran Adhikary (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
In this study, we assessed the outcome of surgical revascularization technique, coronary artery bypass grafting (CABG) with or without coronary endarterectomy for patients with diffuse coronary artery disease in a single surgeons practice on 2,189 patients from January 2009 and December 2016. The variables like intubation time, ICU stay, postoperative myocardial infarction, arrhythmia, renal impairment, stroke and ICU mortality were compared. Among these patients, 1,000 patients required coronary endarterectomy in addition to off-pump coronary artery bypass grafting (OPCABG). Initially, the mortality and incidence of postoperative blood transfusion were higher in the group of patients who had coronary endarterectomy in addition to CABG. However, postoperative combined use of heparin, warfarin and double anti-platelet agent was associated with decreased mortality significantly in our study. In comparison to other group, the patients in the combined coronary endarterectomy with CABG group had a higher incidence of male sex, past myocardial infarction and poor left ventricular function. Total myocardial revascularization is attainable when coronary endarterectomy is performed in addition to off-pump coronary artery bypass graft surgery in diffuse coronary artery disease.